Hi all,
I have the following equations;
0 = A - (B/(50^2))
-8 = A - (B/(75^2))
with the answers as follows;
B = -36000
A = -14.4
I think i may be failing somewhere with my rearranging of the formulas to subtract one from the other.
Any ideas?
Hi all,
I have the following equations;
0 = A - (B/(50^2))
-8 = A - (B/(75^2))
with the answers as follows;
B = -36000
A = -14.4
I think i may be failing somewhere with my rearranging of the formulas to subtract one from the other.
Any ideas?
What do you get if you subtract the second equation from the first?
0- (-8)= 8, of course, and A- A= 0. So what is -B/50^2- (-B/75^2)? (50= 25(2) and 75= 25(3). So 50^2= 25^2(4) while 75^2= 25^2(9). The common denominator is 25^2(4)(9).
with the answers as follows;
B = -36000
A = -14.4
I think i may be failing somewhere with my rearranging of the formulas to subtract one from the other.
Any ideas?[/QUOTE]